How to bridge the last mile in agro-climate service adoption? The importance of farmers' needs, attitudes and interpersonal relations in understanding impact pathways - Thi Thu Giang Luu; Eike Luedeling; Lisa Biber-Freudenberger; Cory Whitney (Environment, Development and Sustainability, 2024)
Climate services can support multiple Sustainable Development Goals. However, in agricultural contexts, the “last-mile” delivery of agro-climate services (ACS) struggles with numerous barriers that prevent smallholder farmers from receiving crucial information. We sought to assess the processes by which farmers adopt ACS in order to support the scaling of ACS. We developed a procedure to serve as a rapid test to provide an overview of impact pathway relations in ACS adoption. We generated ACS adoption pathways through focus group discussions, quantified the overall adoption rate and tested relationships between factors and their causal influence on adoption. To showcase our method, we used the case study of CARE in Vietnam (CVN), a non-governmental organization attempting to improve the provision of ACS to smallholder farmers since 2015. In CVN's projects, ACS were co-generated and subsequently delivered to farmers through structured meetings or on an ad-hoc basis in village meetings. We found that farmers who participated in structured groups were very likely to demand, access, read, discuss, understand, positively perceive and adopt ACS and recommend them to peers. About half of the farmers in non-structured groups continued to have difficulties understanding ACS. Nevertheless, these farmers still had a positive attitude toward ACS. While different impact pathways were attributed to the two groups, they still shared similar adoption rates (98%). The results suggest that adoption of ACS at a critical mass might be sufficient to trigger systemic changes within social groups and interactions between its members. Employing a pathway approach can be beneficial for designing and evaluating development interventions.
Keywords: 330; Agriculture; Climate services; Development; Innovation; Scaling; Decision-making